ANALISIS POTENSI PENGEMBANGAN PETERNAKAN SAPI POTONG DI KABUPATEN PESAWARAN - Juwita Indrya Saputra; Liman ,; Yusuf Widodo (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
The purpose of this study was to observe the development and carrying capacity of beef cattle livestock from several aspects such as the environment, human resources and natural resources. The potential was calculated based on the production and carrying capacity of agricultural residues, cattle capacities and Location Quotient (LQ). This research was carried out at Pesawaran Regency on December 2015 until April 2016. This research used survey method with purposive sampling. The result of this research showed that the potential of natural resources in Pesawaran Regency were 74.234 ha of agricultural land that supported by crop residues production 898.875.420 kg/yr. Based on carrying capacity of crop residues production in Pesawaran regency reached until 393.855 AU with 36.65 worth the carrying capacity Index. By looking at the results of the carrying capacity index calculations in Pesawaran regency, all areas have the potential for the development of beef cattle. Based on the capacity of cattle assuming the provision of rations of 30% as many as 601.385 AU have additional opportunities of 586.107 head of cattles while the rations of 40% as many as 451.039 AU have additional opportunities 435.684 head of cattles. Based on the analysis of Location Quotient (LQ), Negeri Katon and Tegineneng could be base areas of beef cattle livestock breeding. Keywords: Agricultural residues, Beef cattle, Carrying capacity, Location quotient, Pesawaran